Effects of reducing sedentary behavior on liver insulin sensitivity, liver fat content, and liver enzyme levels : a six-month randomized controlled trial - Laine, Saara; Sjöros, Tanja; Garthwaite, Taru; Honka, Miikka-Juhani; Löyttyniemi, Eliisa; Norha, Jooa; Eskola, Olli; Koivumäki, Mikko; Vähä-Ypyä, Henri; Sievänen, Harri; Vasankari, Tommi; Hirvonen, Jussi; et al. (American Physiological Society, 2025)
Metabolic syndrome increases the risk of developing noncommunicable diseases such as metabolic dysfunction-associated steatotic liver disease. The aim was to investigate the effects of sedentary behavior (SB) reduction on liver glucose uptake (LGU), endogenous glucose production (EGP), liver fat content (LFC), and liver enzyme levels [alanine aminotransferase (ALT), aspartate aminotransferase, and γ-glutamyltransferase]. Forty-four sedentary (daily SB time ≥ 10 h), physically inactive middle-aged adults with metabolic syndrome were randomized into intervention (INT; n = 23, 21 completed) and control (CON; n = 21, 19 completed) groups. For 6 mo, INT aimed to limit SB by 1 h/day, whereas CON aimed to maintain usual habits. SB and physical activity (PA) were measured continuously with hip-worn accelerometers. Before and at the end of the intervention, LGU was measured using positron emission tomography during the hyperinsulinemic-euglycemic clamp. EGP was calculated, and LFC was measured by magnetic resonance spectroscopy. INT reduced SB by 51 [95% confidence interval (CI): 22, 78] min/day and increased moderate-to-vigorous physical activity (MVPA) by 22 (95% CI: 12, 33) min/day, with no significant change in CON. Differences in liver health markers between the groups were not significant. However, according to the exploratory analyses among participants who successfully reduced SB, ALT decreased (-1.1 [95% CI: 0.93, 1.36] U/L) compared with the continuously sedentary participants (+0.8 [95% CI: 0.65, 1.05] U/L) (group × time, P = 0.006). To enhance liver health, reducing SB for longer durations and/or increasing the intensity of PA may be necessary. However, successfully reducing SB may lead to better levels of circulating ALT liver enzymes.
NEW & NOTEWORTHY
Aiming to reduce sedentary behavior (SB) by 1 h/day did not significantly influence liver health markers, suggesting that more substantial reductions or a different approach might be necessary to see improvements. However, achieving the desired behavioral change could lead to improvements in ALT levels. This study is the first to analyze how reducing SB and replacing it with nonguided physical activity impacts liver health in adults with metabolic syndrome, offering insights for future intervention strategies.